Managing Innovation in Telecommunication Industry: A Study of Wimax in Taiwan - Chiu, Ping Wei (2009)
Wimax (Worldwide Interoperability for Microwave Access) is gaining much attention from telecommunications industry and is considered as a viable solution for the end-user's all telecommunications needs. This perception of WiMAX is reminiscent of 3G (Third Generation) wireless deployment and acceptance. However, WiMAX is a completely novel technology and is being hailed as a disruptive innovation. It is expected to cause a change in the market positions and market dynamics in the telecommunications sector. This research is therefore aimed at accessing the impact of WiMAX deployment in terms of the strategies used by the new market entrants and the incumbent telecommunication organization in Taiwan. The research also aims at evaluating the key success factors that define the success for the new WiMAX entrants and incumbents using the Christensen (2004) framework to understand the signal of change, the competitions, and attitude of the competitors in the telecommunication industry. The findings of the analysis were used to provide insights and recommendations for the new WiMAX entrants in Taiwan.